1989
DOI: 10.1002/bbpc.19890930706
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and Water Osmotic Flow Coefficients in Nafion Membranes

Abstract: Membranes / Nonequilibrium Phenomena / Osmotic Flow Coefficients / Thermodynamics / Transport Properties The isothermal transport coefficients describing the NaCI, volume and water osmotic flows across Nafion membranes are studied. These transport coefficients and others already reported are used to obtain the L,, phenomenological coefficients related to the flows of ions and water in the membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Let us see this relaxation process in the membrane system composed of a Nafion 120 membrane immersed in a 10 mM aqueous solution of NaCl, as studied by Scibona et al [13][14][15] The coefficients L ij related to this problem are shown in Table I; these coefficients have been calculated in this paper with data provided in Ref. 15, Tables II and III. When we keep I ϭ 0 and ⌬p ϭ 5 ϫ 10 3 Pa constant, the flux J 2 depends exclusively on ⌬c 2 , as we can see in Fig.…”
Section: Relaxation Processesmentioning
confidence: 99%
“…Let us see this relaxation process in the membrane system composed of a Nafion 120 membrane immersed in a 10 mM aqueous solution of NaCl, as studied by Scibona et al [13][14][15] The coefficients L ij related to this problem are shown in Table I; these coefficients have been calculated in this paper with data provided in Ref. 15, Tables II and III. When we keep I ϭ 0 and ⌬p ϭ 5 ϫ 10 3 Pa constant, the flux J 2 depends exclusively on ⌬c 2 , as we can see in Fig.…”
Section: Relaxation Processesmentioning
confidence: 99%
“…We have emphasized before the advantages of the electric current being an independent quantity in the transport equations. Now we need to express j 1 , j + /ν + , and Δψ - in terms of Δμ 1 , Δμ 2 , and I . , A straightforward algebraic manipulation would lead to the phenomenological transport equations which also involves six transport coefficients.…”
Section: Electrodiffusion Processes In Membranesmentioning
confidence: 99%
“…Now we need to express j 1 , j + /ν + , and ∆ψ -in terms of ∆µ 1 , ∆µ 2 , and I. 2,13 A straightforward algebraic manipulation would lead to the phenomenological transport equations which also involves six transport coefficients.…”
Section: Experimental Determination Of the Phenomenologicalmentioning
confidence: 99%